Development of temporal rainfall pattern for Southern Region of Sarawak - Rosmina A., Bustami; Nor Azalina, Rosli; Jethro Henry, Adam; Kuan, Pei Li (Universiti Malaysia Sarawak, (UNIMAS), 2012)
In the process of a design rainfall, information on rainfall duration, average rainfall intensity and temporal rainfall pattern is important. This study focuses on developing a temporal rainfall pattern for the Southern region of Sarawak since temporal pattern for Sarawak is yet to be available in the Malaysian Urban Storm Water Management Manual (MSMA), which publishes temporal pattern for design storms only for Peninsular Malaysia. The recommended technique by the Australian Rainfall and Runoff (AR&R) known as the ‘Average Variability Method’ and method in Hydrological Procedure No.1-1982 are used to derive design rainfall temporal pattern for the study. Rainfall data of 5 minutes interval from year 1998 to year 2006 for 7 selected rainfall stations in the selected region is obtained from Department of Irrigation and Drainage (DID). The temporal rainfall patterns developed are for 10 minutes,15 minutes, 30 minutes, 60 minutes, 120 minutes, 180 minutes and 360 minutes duration. The results show that Southern region of Sarawak has an exclusive rainfall pattern, which is different from the pattern developed for Peninsular Malaysia.